Impact of a virtual antenatal intervention for improved diet and iron intake in Kapilvastu district, Nepal - the VALID randomized controlled trial - Saville, Naomi M.; Bhattarai, Sanju; Giri, Santosh; Sapkota, Suprich; Morrison, Joanna; Thapaliya, Bibhu; Bhattarai, Basudev; Yadav, Samata; Arjyal, Abriti; Copas, Andrew; Haghparast-Bidgoli, Hassan; Harris-Fry, Helen; et al. (Frontiers in Nutrition, 2024)
Counselling can improve anaemia in pregnancy, but few interventions have tested a virtual method of delivery. We hypothesised that a virtual counselling intervention delivered via a mobile device (mHealth) would prevent and treat anaemia, compared with routine antenatal care. Methods Virtual Antenatal Intervention for improved Diet and Iron intake (VALID) was a non-blinded parallel group two-arm individually randomised superiority trial (1:1 allocation). Participants were pregnant women who were married, aged 13-49 years, able to answer questions, 12-28 weeks' gestation and living in Kapilvastu, Nepal. Women were randomised to receive routine antenatal care (ANC) (control arm), or ANC plus a virtual antenatal intervention of two problem-solving counselling sessions via video call. The primary outcome was Iron Folic Acid (IFA) tablet compliance (consumption on 12+ of the previous 14 days). Secondary outcomes were dietary diversity, promoted food consumption, iron bioavailability enhancement, and knowledge of iron-rich foods. Primary logistic regression analysis was by intention-to-treat, adjusting for baseline values.Trial registration: ISRCTN17842200 https://www.isrctn.com/ISRCTN17842200. Status: closed.We enrolled 319 pregnant women (161 control, 158 intervention) from 23 January to 6 May 2022 and analysed outcomes in 144 control and 127 intervention women. Compliance to IFA increased in both arms. In the intervention arm compliance increased by 29.7 percentage points (49.0 to 78.7%) and by 19.8 percentage points in the control arm (53.8 to 73.6%). Despite the larger increase in the intervention arm, we found no intervention effect upon IFA compliance (adjusted Odds Ratio (aOR) 1.33 95% CI 0.75, 2.35, p=0.334), dietary diversity or ANC visits. The intervention increased knowledge of iron-rich foods (coefficient 0.96 (95% CI 0.50, 1 .41), p<0.001), consumption of promoted foods (aOR 1.81 (95% CI 1.08, 3.02), p=0.023), behaviour to enhance iron bioavailability (aOR 4.41 95% CI 1.23, 15.83, p=0.023), 10.54, p=0.004). The total intervention cost was US$35,193 and cost per pregnant woman receiving two virtual counselling sessions was US$277.Virtual counselling can improve some antenatal health behaviours such as consumption of promoted foods and methods to improve bioavailability. Improved IFA consumption and ANC attendance may require additional family/community support.